Development of scientific thought about the content of the concept of «evidence» in the civil process - Грабовська, О. О.; Чепак , І. В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2018)
Evidence of legal facts and circumstances, without exaggeration, is the basis of procedural activity, it is evident that the content of the concept of «evidence» excited the representatives of the procedural sciences at all times of their development. An analysis of scientific sources indicates a deeper level of scientific research of the concept of «evidence» in criminal-process science. Civil procedural science is not typical. At the same time, in the last period of time there were fundamental works devoted to civil procedural proof in which the authors could not ignore the concept of «evidence». So, in monograph Grabovska O. O. reveals the concept of «evidence» from two points: as a tool for proving facts and circumstances by legally interested parties – participants in the case, and a source of knowledge and conditionalities about the facts and circumstances that are established by the court. Andreytsy V. D. directs his attention to the peculiarities of the court’s interaction with evidence at various stages of civil justice, in particular, at the stage of gathering evidence, their submission, research, etc. Despite the presence of a large number of conclusions and views on evidence, the scientific search for the most successful model of the concept of «evidence» continues, which is due not only to the development of procedural scientific thought, taking into account the conclusions of representatives of various sciences, but also the development of procedural legislation, in particular, civil procedural. Adopted in 2017, a new version of the Civil Procedural Code of Ukraine requires a scientific reflection on the systemic changes that took place in the regulation of the implementation of civil justice, including the regulation of the institute of evidence, evidence as a means by which the facts and circumstances are established. The author of the article aims to find the answer to the question about the content of the concept of «evidence», the ability to display in it as many components that reflect the nature of the genesis of the development of scientific conclusions about this legal phenomenon, as well as regulation of the existing procedural law. Logical in this sense is an analysis of historical sources that have survived to this day and are an invaluable legacy for contemporary researchers. The author proposes the actual definition of the concept of «evidence» – the data on the facts and circumstances provided by the parties and other parties to the case in order to justify the claims and objections in accordance with the subject of evidence, are directly recognized and accepted by the court as a result of their research and evaluation.

Доказування юридичних фактів та обставин, без перебільшення, основа процесуальної діяльності. Очевидно, саме тому зміст поняття «доказ» хвилював представників процесуальних наук у всі часи їх розвитку. Аналіз наукових джерел свідчить про більш глибокий рівень наукових досліджень концепту «доказ» у кримінально-процесуальній науці. Цивільній процесуальній науці це не характерно. Водночас, в останній період часу з’явилися фундаментальні праці, присвячені цивільному процесуальному доказуванню, в яких автори не могли обійти увагою поняття «доказ». Розвитком наукової думки про зміст поняття «докази» у кінці ХІХ – на початку ХХ ст. займалися, зокрема, С. Н. Абрамов, Е. В. Васьковський, Ю. С. Гамбаров, К. І. Малишев, К. С. Юдельсон, Т. М. Яблочков та ін. На сучасному етапі більш ґрунтовному дослідженню цього питання присвятили свої праці такі зарубіжні та вітчизняні вчені, як В. П. Гмирко, О. О. Грабовська, О. С. Захарова, Т. М. Кучер, М. А. Погорецький, І. В. Решетнікова, С. Я. Фурса та інші. Проте, незважаючи на наявність значної кількості висновків та поглядів про докази, науковий пошук найбільш вдалої моделі поняття «доказ» продовжується, що викликано не лише розвитком процесуальної наукової думки, урахуванням висновків представників різних наук, а й розвитком процесуального законодавства, зокрема, цивільного процесуального. Прийнята у 2017 р. нова редакція Цивільного процесуального кодексу України потребує наукового осмислення системних змін, що відбулись у регулюванні здійснення цивільного судочинства, в тому числі й регулюванні інституту доказування, доказів як засобів, за допомогою яких встановлюються факти та обставини. Автором статті поставлено за мету пошук відповіді на питання про зміст поняття «доказ», можливість відобразити у ньому якомога більше складових, які вказують на сутність з урахуванням генези розвитку наукових висновків про це правове явище, а також регулювання чинним процесуальним законодавством. Логічним у цьому сенсі видається аналіз історичних джерел, які збереглися до нашого часу і є неоціненною спадщиною для сучасних дослідників. Автором запропоновано власне визначення поняття «докази» – це дані про факти та обставини, які надані сторонами та іншими учасниками справи з метою обґрунтування вимог та заперечень відповідно до предмета доказування, безпосередньо визнані та прийняті судом унаслідок їх дослідження та оцінки.
РОЗВИТОК НАУКОВОЇ ДУМКИ ПРО ЗМІСТ ПОНЯТТЯ «ДОКАЗИ» У ЦИВІЛЬНОМУ ПРОЦЕСІ
Keywords: evidence; evidence; civil process; civil justice.; докази; доказування; цивільний процес; цивільне судочинство.